Engaging customer cocreation in new product development through foreign subsidiaries : influences of multinational corporations’ global integration and local adaptation mechanisms - Leung, Fine F. (2021)
Efforts to engage customers in cocreating new products have garnered much research attention from studies documenting customer cocreation’s (CC’s) positive impact on firm innovation and performance. Less research, however, has counterbalanced the bright side with the potential dark side of CC, especially as a strategy for multinational corporations (MNCs) operating in foreign markets. This study examines how MNC subsidiaries’ CC affects new product innovativeness and knowledge leakage to competitors. Adopting a broader agency perspective to recognize that subsidiaries often do not perform up to headquarters’ expectations due to both self-serving opportunism and honest incompetence, this study explores how CC effects are contingent on MNCs’ global management mechanisms. Using a dyadic managerial survey of 238 MNC subsidiaries, the authors find that MNCs can control knowledge leakage by implementing proper global integration and local adaptation mechanisms. However, CC may not improve new product innovativeness, except when the subsidiary has low local research-and-development staff influence. This study contributes to the CC literature by showing its benefits, challenges, and boundary conditions as a growing MNC innovation strategy.